The Effect of Baby Massage on Sleep Quantity in Infants Aged 6-12 Months With Cough and Cold - Firdawanti, Wahyu Asih Winda; Umami, Nurrahmi; Sari, Agus Purnama (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2024)
Sleep quantity is very important for infant growth and development. If the baby’s sleep quantity is poor, it can cause the baby’s physiology and psychology to be disturbed. In infant with cough and cold, the most common problem is sleeping disturbance. One of the non-pharmacological therapies that can be given to babies who are coughing and cold is baby massage. Baby massage can also cause a decrease in alpha waves and beta waves, so that theta waves will increase. This study aims to determine the effect of baby massage on the quantity of sleep-in infant aged 6-12 months with a cold cough in the working area of Karang Rejo Health Centre, Tarakan. This research was quantitative research with quasi experimental design pre and post with out control. The population in this study amounted to 124 babies. The sample size was 33 respondents. The result showed the quantity of sleep infants aged 6-12 month with a cold cough before being given a massage intervention 33 infant (100percent) with a bad category, after being given a baby massage intervention the quantity of sleep of infant aged 6-12 months with a cold cough increased to a good category namely 27 infants (81,8percent). Bivariate analysis Wilcoxon test showed p-value= 0,001 (p-value less than 0,05) which means that there was an effect of giving baby massage on the quantity of sleep of infant aged 6-12 months with a cold cough in the working area of Karang Rejo Health Centre, Tarakan.